2018
DOI: 10.1002/jcp.27013
|View full text |Cite
|
Sign up to set email alerts
|

AhR ligand aminoflavone suppresses α6‐integrin–Src–Akt signaling to attenuate tamoxifen resistance in breast cancer cells

Abstract: More than 40% of patients with luminal breast cancer treated with endocrine therapy agent tamoxifen demonstrate resistance. Emerging evidence suggests tumor initiating cells (TICs) and aberrant activation of Src and Akt signaling drive tamoxifen resistance and relapse. We previously demonstrated that aryl hydrocarbon receptor ligand aminoflavone (AF) inhibits the expression of TIC gene α6-integrin and disrupts mammospheres derived from tamoxifen-sensitive breast cancer cells. In the current study, we hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…Recent work demonstrated that AF inhibits the expression of α6‐integrin expression; the overexpression of these cell adhesion molecules is associated with tumor initiation cell proliferation, malignant breast cancer, and poor prognosis . Additionally, α6‐integrin overexpression is related to breast cancer resistance to radiotherapy, as well as tamoxifen resistance . AF reduces the expression of α6‐integrin in both tamoxifen‐resistant MCF‐7 and BT474 cells, inhibiting the α6‐integrin‐Src‐Akt signaling pathway, countering tamoxifen resistance in these ER‐positive cell lines …”
Section: Exogenous Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work demonstrated that AF inhibits the expression of α6‐integrin expression; the overexpression of these cell adhesion molecules is associated with tumor initiation cell proliferation, malignant breast cancer, and poor prognosis . Additionally, α6‐integrin overexpression is related to breast cancer resistance to radiotherapy, as well as tamoxifen resistance . AF reduces the expression of α6‐integrin in both tamoxifen‐resistant MCF‐7 and BT474 cells, inhibiting the α6‐integrin‐Src‐Akt signaling pathway, countering tamoxifen resistance in these ER‐positive cell lines …”
Section: Exogenous Ligandsmentioning
confidence: 99%
“…Additionally, α6‐integrin overexpression is related to breast cancer resistance to radiotherapy, as well as tamoxifen resistance . AF reduces the expression of α6‐integrin in both tamoxifen‐resistant MCF‐7 and BT474 cells, inhibiting the α6‐integrin‐Src‐Akt signaling pathway, countering tamoxifen resistance in these ER‐positive cell lines …”
Section: Exogenous Ligandsmentioning
confidence: 99%
“…Genistein can confer sensitivity to triple-negative breast cancer for antiestrogen therapy by preventing and reversing AhR-dependent BRCA1 hypermethylation [39]. Aminoflavone, another AhR ligand, inhibits the proliferation of tamoxifen-resistant cells by suppressing α6-integrin-Src-Akt signaling [40]. Raloxifene induces apoptosis mediated by AhR in ER-negative BC cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated that collagen/integrin β1/Src signal transduction was a key regulatory pathway that mediated the resistance of HER2 + breast cancer to anti-HER and anti-PI3K inhibitor combination therapy. In addition to integrin β1, another study found that activation of the integrin α6/Src/Akt signal transduction pathway mediated the resistance of breast cancer cells to tamoxifen ( Campbell et al., 2018 ). Upregulation of integrin α6 was found both in tamoxifen-resistant breast cancer cells and tumor tissue sections from patients who relapsed on tamoxifen treatment ( Campbell et al., 2018 ).…”
Section: Integrins and Cancer Drug Resistancementioning
confidence: 99%